Pengaruh Kepemilikan Manajerial, Kepemilikan Institutional, dan Kepemilikan Publik Terhadap Manajemen Laba - Agnes Dyah Utami; Dian Indriana Hapsari (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This study aims to determine the impact of managerial ownership, institutional ownership, and public ownership on income control. There were 23 samples that were decided according to the applicable criteria. The record evaluation technique used in this study was purposive sampling. The test uses conventional speculation trials and more than one regression evaluation. The results show that managerial ownership and institutional ownership have an impact on earnings management, and public ownership has no impact on earnings management.